Narrowing the post-COVID development gap within ASEAN - Pitakdumrongkit, Kaewkamol (2023)
The economic impact of the COVID-19 pandemic on the ASEAN Member States has been negative and uneven. There is a need to close the development gap within ASEAN in order to accelerate the implementation of the envisioned ASEAN Economic Community.